2002
DOI: 10.1007/s00421-002-0688-z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of whole-body and local thermal stress on hydrostatic volume changes in the human calf

Abstract: In the present study, we examined the effect of thermal stress on the magnitude and pattern of change in leg volume during orthostatic stress and thigh occlusion in humans. Ten healthy volunteers underwent whole-body thermal stress produced by a cool- or hot-water-perfused suit and local heat stress of the calf. During whole-body thermal stress, changes of calf circumference during head-up tilt (HUT) at angles of 15 degrees and 60 degrees for 2 min each were monitored. In the supine position, the distensibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 21 publications
1
10
0
1
Order By: Relevance
“…We (4) and others (11) have shown that the increase in leg circumference during LBNP is significantly smaller with skin surface cooling compared with normothermic conditions. Similar responses have also been reported during head-up tilt with cooling (19). These data suggest that central blood volume under cooling conditions may remain relatively higher during orthostatic stress.…”
Section: Discussionsupporting
confidence: 73%
“…We (4) and others (11) have shown that the increase in leg circumference during LBNP is significantly smaller with skin surface cooling compared with normothermic conditions. Similar responses have also been reported during head-up tilt with cooling (19). These data suggest that central blood volume under cooling conditions may remain relatively higher during orthostatic stress.…”
Section: Discussionsupporting
confidence: 73%
“…Whole-body heating induces cutaneous venodilatation in the legs and arms 46,47) and decreases muscle venous volume as a percentage of the total volume of leg veins with an increase in skin venous volume. Compared with normothermic control, whole-body heating rapidly increases calf volume during the early phase of HUT, whereas whole-body cooling decreases the magnitude and the speed of change in calf volume 48) . Local heating to the legs in normothermia increases the blood flow in the warmed skin area and increases the speed of the change in calf volume the same nique, the effect of heat stress on the relationship between carotid distending pressure and HR has been examined in the supine position [50][51][52] .…”
Section: Increase In Leg Venous Compliancementioning
confidence: 99%
“…arterial pressure = HR × SV × total PVR), and the use of HR may be better for evaluating baroreflex sensitivity in the maintenance of arterial pressure. In a study as that during whole-body heating 48) . That is, the thermal modulation in leg venous distensibility is almost independent of whole-body or local heating.…”
Section: Increase In Leg Venous Compliancementioning
confidence: 99%
“…In each thermal condition, we abruptly occluded the thigh at 20, 30, 50, 70, and 80 mmHg in this order in five subjects and in the opposite order in the remaining subjects. This enabled us to study the vascular response and swelling pattern of the calf over a wide range of transmural venous pressures, such as those that occur during changes in posture or tilt [17]. That is, we used this method to examine the isolated effect of local reflex in vasoconstriction in the lower extremities during HUT.…”
Section: Subjectsmentioning
confidence: 99%
“…Between each occlusion pressure, the thigh cuff pressure was abruptly released to zero by opening the inflation bulb. The criterion for deflating the cuff was either (i) when the increase of calf circumference reached a steady-state level or (ii) when its increase was less than 0.5 mm for 30 s [17,18]. The first was mainly used for the cuff pressures of 20, 30, and 50 mmHg, at which the calf circumference reached a steady state within 1-4 min.…”
Section: Subjectsmentioning
confidence: 99%